Implementation of power management based on fuzzy logic for a hybrid PV/Fuel Cell generation system - M. Sellali; A. Betka; S. Drid; A. Djerdir; M. Tiar; S. Abdedaim (International Conference On Emerging and Renewable Energy : Generation and Automation, Sousse-Tunisia, 2018)
The present paper deals with a real time implementation of a new adaptive frequency-based power management strategy of a small-scale hybrid battery-super capacitor system, dedicated to an electric vehicle. The ultimate objective of the strategy is to ensu